A Spatial Optimization Framework for Bus Stop Locations: Enhancing Urban Mobility in Jember - Alfiah, Rindang; Graha, I Made Satya; Listyawati, Ratih Novi; Zafira, Nurul (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2026)
Jember's urban area has experienced economic development and has become the third-largest educational hub in East Java. To address the transportation congestion caused by large activities in urban areas, an effective and affordable public transportation system is essential. The coverage of bus stops plays a key role, as evident from their proximity to residential and public areas, as well as the reach of passengers. This research aims to evaluate the coverage of bus stops in the Jember urban area and optimize the locations of new stops. Using the network analyst service area, buffer area, and kernel density, the research defines service coverage within a 400-meter area based on a person's willingness to walk. Additionally, the scoring method used to evaluate the feasibility of bus stops is based on the standardization of bus stop design. The results show that 10 bus stops are not suitable for standardization, while the other nine are moderately suitable. Currently, only 48.7% of the urban area is served by public transport stops. The studies proposed 12 new bus stop locations, which will increase the coverage area to 79.1% and cover 216 out of 273 identified facilities.